Jobs with green potential in Switzerland: Demand and possible skills shortages - Michael Lobsiger; Christian Rutzer (University of Basel, Center of Business and Economics (WWZ), 2021)
We use a data-driven methodology to quantify the importance of different skills in performing green tasks. For Switzerland, we estimate the green potential to be 16.7% of the total of employed persons and 18.8% of full-time equivalents in 2017, respectively. Employed persons in jobs with high green potential are, on average, younger, more often men, have a higher level of educational attainment and a higher probability of having immigrated than employed persons in other occupations. Moreover, there is a shortage of skilled labour in the group of jobs with high green potential, particularly pronounced for the occupational groups managers and professionals. In light of the already tense situation for skilled workers in jobs with high green potential and the expected increase in demand for these occupations, increased efforts will be necessary, especially in the area of labour qualication (education as well as post-qualication and upgrading), to meet the demand for skilled workers for the transition to a sustainable economy.
Keywords: J23; J24; Q52; 330; green transition; labor market; skills shortage